GEOLOGY AND ORIGIN OF SAND RIDGES IN A BACK-BARRIER ESTUARY, PAMLICO SOUND, NORTH CAROLINA - Querry, Brian K. (East Carolina University, 2018)
The Outer Banks of North Carolina have undergone significant geomorphic change, exhibiting varying degrees of barrier island continuity during the late Holocene. These changes affect the environmental conditions (salinity, tidal and wave energy, currents, etc.) in Pamlico Sound, the estuarine system behind the Outer Banks. The modern estuarine system is characterized by minimal tidal energy (tidal range of approximately 10 cm) and limited exchange with the marine environment through three inlets, resulting in the accumulation of organic-rich muds in the Pamlico Sound basin, containing mid- to high- salinity estuarine foraminifera. However, a sand ridge field occurs at approximately 2 to 7 m below sea level in the eastern Pamlico Sound basin, suggesting different hydrodynamic conditions at some time during the Holocene. The sand ridge field extends up to 10 km into the basin, and is oriented perpendicular to the barrier islands. Previous paleoenvironmental work suggests the sand ridges were deposited under high salinity conditions. Defining the mechanism of formation of this sand ridge field will assist in understanding the geological evolution of the region. Six vibracores and 60 km of chirp sub-bottom profiler data have been acquired in order to characterize this system. Two foraminiferal biofacies were identified, High Brackish biofacies A (more diverse) and High Brackish biofacies B (less diverse). To understand the geologic history and origin of this sand ridge field, the cored sediments were analyzed for sedimentology, foraminiferal assemblages, bulk magnetic susceptibility, and geochronology. Chirp seismic data were examined to understand the dimensions and stratigraphy of the sand ridges. Surface samples were collected to understand the modern sedimentology. Vibracores reveal that the sand ridge sediments generally lack mud and have a greater average grain-size farther into Pamlico Sound (i.e., distal to the barrier islands) suggesting that the barrier islands are not the source of the sand. Chirp seismic data delineate a Pleistocene interfluve underlying the sand ridges. Geochronology indicates that sand ridge formation began at approximately 2500 cal yr. BP. There are two intervals at 1000 cal yr. BP and 500 cal yr. BP where an increase in wave and current activity is suggested by seismic horizons. Seismically, the top of the Pleistocene interfluve exhibits two topographic highs that demonstrate the sand ridges are juvenile Class I sand ridges. The sand ridges are interpreted as resulting from the reworking of Pleistocene interfluves during intervals of increased tidal influence and possibly storm activity where winds speeds are 20 mph or greater.
Keywords: Earth Science; Paleo-environments; Hatteras; Barrier islands--North Carolina--Pamlico Sound; Sand waves--North Carolina--Pamlico Sound; Geology, Stratigraphic--Holocene